Do Hub-and-Spoke Free Trade Agreements Increase Trade? A Panel Data Analysis - Joseph Alba; Jung Hur; Donghyun Park (Asian Development Bank (ADB), 2010)
We use panel data consisting of 96 countries and covering the period 1960–2000 to investigate the effects of free trade agreements (FTAs) and hub-and-spoke systems of FTAs on exports. Our empirical results imply an annual growth rate of 5.57% in exports, leading to a doubling of exports after 12.4 years, between FTA partners. Non-overlapping FTAs account for 4.12%, while hub-and-spoke FTAs account for 1.45% of the estimated export growth rate. This indicates that in addition to the direct trade liberalizing effect of FTAs, the hub-and-spoke nature of FTAs has an additional positive effect on trade.
hdl:11540/1958
Keywords: F15; 330; free trade agreement; hub and spoke; world bilateral trade data; panel data analysis; fixed effect; average treatment effect